VUV-UV-vis photoluminescence, X-ray radioluminescence and energy transfer dynamics of Ce3+ and Eu2+ in Sr2MgSi2O7. Issue 46 (10th November 2022) - Wen, Donghao; Li, Quanfeng; Ou, Yiyi; Yang, Yunlin; Qi, Zeming; Dorenbos, Pieter; Liang, Hongbin
Abstract : The VUV-UV-vis photoluminescence, X-ray radioluminescence, energy transfer dynamics of Ce 3+ and Eu 2+ in Sr2 MgSi2 O7 and the dependencies of Ce 3+ 4f–5d transitions on the local structure of Sr2 MgSi2 O7, Ba2 MgSi2 O7 and BaMg2 Si2 O7 are discussed. Abstract : Ce 3+ and Eu 2+ doped and Ce 3+ –Eu 2+ co-doped Sr2 MgSi2 O7 phosphors are prepared via a high-temperature solid-state reaction technique. The synchrotron radiation vacuum ultraviolet-ultraviolet (VUV-UV) excitation and ultraviolet-visible (UV-vis) emission spectra of diluted Ce 3+ and Eu 2+ doped Sr2 MgSi2 O7 samples are measured at cryogenic temperatures. The electron-vibrational interaction (EVI) between Ce 3+ and its surroundings is analyzed. The dependencies of the 4f–5d transitions of Ce 3+ on the structure of the host compounds Sr2 MgSi2 O7, Ba2 MgSi2 O7 and BaMg2 Si2 O7 are discussed in detail. Then the thermal quenching channel is proposed based on the measurements of temperature dependent luminescence intensities and decay times of Ce 3+ and Eu 2+ in Sr2 MgSi2 O7, and the Ce 3+ → Eu 2+ energy transfer mechanism is understood by three luminescence dynamic models. In addition, Sr2 MgSi2 O7 :Ce 3+ /Eu 2+ samples are evaluated for the possibilities of X-ray detection applications using X-ray excited luminescence (XEL) spectroscopy, and it was found that they are not suitable.